Inaccurate Saccades and Enhanced Vestibulo-Ocular Reflex Suppression during Combined Eye–Head Movements in Patients with Chronic Neck Pain: Possible Implications for Cervical Vertigo - Johnston, Janine L.; Daye, Pierre M.; Thomson, Glen T. D. (Frontiers in Neurology, 2017)
Background: The primate ocular motor system is designed to acquire peripheral targets of interest by co-ordinating visual, vestibular and neck muscle activation signals. The vestibulo-ocular reflex (VOR) is greatly reduced at the onset of large eye-head (gaze) saccades and resumes before the end of the saccades to stabilize eye-in-orbit and ensure accurate target acquisition. Previous studies have relied on manipulating head movements in normal individuals to study VOR suppression and gaze kinematics. We sought to determine if reduced head-on-trunk movement alters VOR suppression and gaze accuracy similar to experiments involving normal subjects and if intentionally increasing head and neck movement affects these dynamics. Methods: We measured head and gaze movements using magnetic search coil oculography in eight patients with cervical soft tissue disorders and seven healthy subjects. All participants made horizontal head-free saccades to acquire a laser dot target that stepped pseudorandomly 30-65 deg to either side of orbital midposition, first using typical head and eye movements and again, after being instructed to increase head amplitudes as much as possible. Results: Compared to health subjects, patients made smaller head movements which contributed only 6% to total gaze saccade amplitudes. Head movements were also slowed, prolonged and delayed. VOR suppression was increased and prolonged. Gaze saccades were inaccurate and delayed with long durations and decreased peak velocities. Conclusions: In patients with chronic neck pain, the internal commands issued for combined eye-head movements have large enough amplitudes to create accurate gaze saccades, however because of increased neck stiffness and viscosity, the head movements produced are smaller, slower, longer and more delayed than they should be. VOR suppression is disproportionate to the size of the actual gaze saccades because sensory feedback signals from neck proprioceptors are non-veridical, likely due to prolonged coactivation of cervical muscles. The outcome of these changes in eye-head kinematics is head-on-trunk stability at the expense of gaze accuracy. In the absence of vestibular loss, the practical consequences may be dizziness (cervical vertigo) in the short term and imbalance and falls in the long term.